Designed To React: Terminal Copper Nitrenes and Their Application in Catalytic C−H Aminations. Issue 29 (19th June 2018) - Moegling, Julian; Hoffmann, Alexander; Thomas, Fabian; Orth, Nicole; Liebhäuser, Patricia; Herber, Ulrich; Rampmaier, Robert; Stanek, Julia; Fink, Gerhard; Ivanović‐Burmazović, Ivana; Herres‐Pawlis, Sonja
Abstract: Heteroscorpionate ligands of the bis(pyrazolyl)methane family have been applied in the stabilisation of terminal copper tosyl nitrenes. These species are highly active intermediates in the copper‐catalysed direct C−H amination and nitrene transfer. Novel perfluoroalkyl‐pyrazolyl‐ and pyridinyl‐containing ligands were synthesized to coordinate to a reactive copper nitrene centre. Four distinct copper tosyl nitrenes were prepared at low temperatures by the reaction with SO2 t BuPhINTs and copper(I) acetonitrile complexes. Their stoichiometric reactivity has been elucidated regarding the imination of phosphines and the aziridination of styrenes. The formation and thermal decay of the copper nitrenes were investigated by UV/Vis spectroscopy of the highly coloured species. Additionally, the compounds were studied by cryo‐UHR‐ESI mass spectrometry and DFT calculations. In addition, a mild catalytic procedure has been developed where the copper nitrene precursors enable the C−H amination of cyclohexane and toluene and the aziridination of styrenes. Abstract : Four distinct terminal copper nitrenes were stabilised at low temperatures through the use of heteroscorpionate ligands of the bis(pyrazolyl)methane family. They were characterised by UV/Vis spectroscopy, cryo‐UHR‐ESI mass spectrometry, and DFT calculations, and employed as catalysts for the C−H amination of cyclohexane and toluene and the aziridination of styrenes.